Why is the Existence of Indigenous People not Recognised in Africa? A Case Study: Bubis of Bioko Island - Juanena, Coro J-A (Revista de Antropología Social, 2016)
European African studies traditionally deny the existence of indigenous communities in Africa, despite the fact that in the same way as the American continent, Africa was once too a region colonised by Europe. The new social and historical identities created under the coloniality of power (Quijano, 2000), endure in the political and academic imagination to the extent of negating the current indigenous status of a large proportion of African nations. This issue is of great relevance in contemporary international politics due to the revival of the idea of the indigenous identity on a global scale and as an answer to modern capitalism, as reinforced by the United Nations Declaration on the Rights of Indigenous Peoples adopted by the UN General Assembly in 2007. My objective of this article is to deconstruct the historical processes that have resulted in the current denial of the existence of indigenous peoples on the African continent.I propose a descriptive study of the Bubi community on the isle of Bioko, an ethnic group which is presently declaring its status as indigenous peoples and asserting its inherent rights in the global arena. This case is especially interesting as a study objective because on the one hand, the first “colonial encounter” of this African nation happens at the same time as it does in the geocultural id-entity called America and, on the other hand, although at different points in history, the effective colonisation of the territory and the designation of the peoples as indigenous is carried out in both cases by the same geocultural id-entity, namely Iberian Europe.
Keywords: Identity; indigenous; coloniality of power; ideology of representation; Bubee.